Parenting for Lifelong Health: a pragmatic cluster randomised controlled trial of a non-commercialised parenting programme for adolescents and their families in South Africa - Cluver, L.; Meinck, F.; Steinert, J.; Shenderovich, Y.; Doubt, J.; Herrero Romero, R.; Lombard, C.; Redfern, A.; Ward, C.; Tsoanyane, S.; Nzima, D.; Sibanda, N.; et al. (2018)
Objective: To assess the impact of ‘Parenting for Lifelong Health: Sinovuyo Teen’, a parenting programme for adolescents in low-income and middle-income countries, on abuse and parenting practices. Design: Pragmatic cluster randomised controlled trial. Setting: 40 villages/urban sites (clusters) in the Eastern Cape province, South Africa. Participants: 552 families reporting conflict with their adolescents (aged 10–18). Intervention: Intervention clusters (n=20) received a 14-session parent and adolescent programme delivered by trained community members. Control clusters (n=20) received a hygiene and hand-washing promotion programme. Main outcome measures: Primary outcomes: abuse and parenting practices at 1 and 5–9 months postintervention. Secondary outcomes: caregiver and adolescent mental health and substance use, adolescent behavioural problems, social support, exposure to community violence and family financial well-being at 5–9 months postintervention. Blinding was not possible. Results: At 5–9 months postintervention, the intervention was associated with lower abuse (caregiver report incidence rate ratio (IRR) 0.55 (95% CI 0.40 to 0.75, P<0.001); corporal punishment (caregiver report IRR=0.55 (95% CI 0.37 to 0.83, P=0.004)); improved positive parenting (caregiver report d=0.25 (95% CI 0.03 to 0.47, P=0.024)), involved parenting (caregiver report d=0.86 (95% CI 0.64 to 1.08, P<0.001); adolescent report d=0.28 (95% CI 0.08 to 0.48, P=0.006)) and less poor supervision (caregiver report d=−0.50 (95% CI −0.70 to −0.29, P<0.001); adolescent report d=−0.34 (95% CI −0.55 to −0.12, P=0.002)), but not decreased neglect (caregiver report IRR 0.31 (95% CI 0.09 to 1.08, P=0.066); adolescent report IRR 1.46 (95% CI 0.75 to 2.85, P=0.264)), inconsistent discipline (caregiver report d=−0.14 (95% CI −0.36 to 0.09, P=0.229); adolescent report d=0.03 (95% CI −0.20 to 0.26, P=0.804)), or adolescent report of abuse IRR=0.90 (95% CI 0.66 to 1.24, P=0.508) and corporal punishment IRR=1.05 (95% CI 0.70 to 1.57, P=0.819). Secondary outcomes showed reductions in caregiver corporal punishment endorsement, mental health problems, parenting stress, substance use and increased social support (all caregiver report). Intervention adolescents reported no differences in mental health, behaviour or community violence, but had lower substance use (all adolescent report). Intervention families had improved economic welfare, financial management and more violence avoidance planning (in caregiver and adolescent report). No adverse effects were detected. Conclusions: This parenting programme shows promise for reducing violence, improving parenting and family functioning in low-resource settings.